ANALISIS KINERJA EKSPOR KOMODITAS UNGGULAN DAN PERTUMBUHAN EKONOMI DAERAH SULAWESI TENGAH - Achmad, Nuryana Haprin Dj. (Katalogis, 2015)
The purposes of this study as follow: firstly, to determine the contribution of export commodities regional economic growth in Central Sulawesi; secondly, to determine the contribution of Central Sulawesi total exports to the economic growth of Central Sulawesi; thirdly, to determine the magnitude of the leading commodity exports of Central Sulawesi to the total exports of Central Sulawesi; lastly, to determine the effect of commodity exports on the regional economic growth of Central Sulawesi. This study apply RCA (Revealed Comparative Advantage) analysis to identify the main commodity. Then, this study is purposed to answer the contribution of main export commodity to economic growth by using contributions analysis, and this study is also conducted to identify the impact of exports on economic growth by usingthe simple regression.  The result shows that the leading commodity has a substantial contribution to economic growth in which the largest contribution of cocoa with 14.7 per cent in 2010. The total contribution of Central Sulawesi export on regional economic growth in the period 2002-2013 was lower compare to the period 2010. The economic growth in the period 2002-2003 shows that the value was fluctuated with the average contribution of 10.4 per cent. Meanwhile, the largest contribution was occurred in 2009 with 18.49 percent. This study found that cocoa is the leading commodity with the range of contribution between 11,3- 94,2 per cent in the period 2002-2013. Furthermore, simple regression shows that the Central Sulawesi commodity exports (independent variable) has positive correlation, but not significant, to         the dependent  variable swith  1,964.